17 amendments of the Pakistani constitution - O. A. Popadyuk (Vestnik MGIMO-Universiteta)
Since its foundation Pakistan has passed a unique path of constitutional and legal development. Through this period 3 Constitutions were adopted, the latest, proclaimed in 1973, is still in force. It was amended for several times. These amendments changed the sense of Constitution drastically. The article analyzes 17 amendments of Pakistani constitution, legal consequences of their adoption, and patterns of constitutional and legal developments in Pakistan.